In Vivo Radioprotective Activity of Cell-Permeable Bifunctional Antioxidant Enzyme GST-TAT-SOD against Whole-Body Ionizing Irradiation in Mice. (19th July 2017) - Pan, Jianru; He, Huocong; Su, Ying; Zheng, Guangjin; Wu, Junxin; Liu, Shutao; Rao, Pingfan
Abstract : GST-TAT-SOD was the fusion of superoxide dismutase (SOD), cell-permeable peptide TAT, and glutathione-S-transferase (GST). It was proved to be a potential selective radioprotector in vitro in our previous work. This study evaluated the in vivo radioprotective activity of GST-TAT-SOD against whole-body irradiation. We demonstrated that intraperitoneal injection of 0.5 ml GST-TAT-SOD (2 kU/ml) 2 h before the 6 Gy whole-body irradiation in mice almost completely prevented the splenic damage. It could significantly enhance the splenic antioxidant activity which kept the number of splenic white pulp and consequently resisted the shrinkage of the spleen. Moreover, the thymus index, hepatic antioxidant activity, and white blood cell (WBC) count of peripheral blood in irradiated mice pretreated with GST-TAT-SOD also remarkably increased. Although the treated and untreated irradiated mice showed no significant difference in the growth rate of animal body weight at 7 days postirradiation, the highest growth rate of body weight was observed in the GST-TAT-SOD-pretreated group. Furthermore, GST-TAT-SOD pretreatment increased resistance against 8 Gy whole-body irradiation and enhanced 30 d survival. The overall effect of GST-TAT-SOD seemed to be a bit more powerful than that of amifostine. In conclusion, GST-TAT-SOD would be a safe and potentially promising radioprotector.